2020
DOI: 10.3389/fphy.2020.573694
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the Stopping Power Effect on Proton-Boron11 Nuclear Fusion Chain Reactions

Abstract: A proton beam with a velocity of the order of 10 9 cm/s is generated to interact with a charge neutral hydrogen-boron medium such as H 3 B. The created charged particles are confined by magnetic fields. This concept was the basis for a novel non-thermal fusion reactor, published recently in Laser and Particle Beams [1]. The fusion is initiated by protons followed by a process of chain reactions in a neutral medium density of the order of 10 19 cm −3 , heated by the pB 11 fusion created alphas up to a temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Eliezer et al [10] analyzed the situations when reaction (1) occurs in gaseous H 3 11 B or other hydride of 11 B with a density of 10 19 cm −3 or of the order of 10 19 cm −3 and temperature of about 1 eV or few eV. Ionization of this gas is supposed negligible [10].…”
Section: The Upper Boundary Of Gmentioning
confidence: 99%
See 4 more Smart Citations
“…Eliezer et al [10] analyzed the situations when reaction (1) occurs in gaseous H 3 11 B or other hydride of 11 B with a density of 10 19 cm −3 or of the order of 10 19 cm −3 and temperature of about 1 eV or few eV. Ionization of this gas is supposed negligible [10].…”
Section: The Upper Boundary Of Gmentioning
confidence: 99%
“…is compensation should increase the probability of participation of the protons in reaction (1) and that of "useful" acceleration of protons due to the scattering of alpha particles on them. e magnetic field should provide the realization of these scenarios in reactors with acceptable sizes [9,10]. Below, it is shown that in the scenario proposed in [10], the ratio g of energy release of reaction (1) to the average value 〈W s 〉 of the energy spent for the initiation of one reaction (1) will be unacceptably low for power production.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations